Application of the hierarchical process analysis (AHP) method in the evaluation of suppliers in a pharmaceutical distributor: a case study - Silva, Joanna da Souza; Licar, Leilde Vieira; Gonçalves, Evelly Cristiane Guimarães; Nunes, Denilson Ricardo de Lucena (Brazilian Journal of Production Engineering, 2025)
The research sought to identify the priority criteria for choosing suppliers of a drug distributor, using the AHP (Analytic Hierarchy Process) method. Through an exploratory case study, three main criteria were analyzed: Quality, Lead Time and After-Sales Relationship, defined by logistics operations managers. The results pointed to Lead Time as the most relevant criterion. The supplier FNR-06 obtained the highest score (8.1737), standing out in Lead Time and After-Sales Relationship, while FNR-08 presented the lowest score (7.0559) due to the unsatisfactory performance in Lead Time. The overall ranking showed that all vendors evaluated are between "Moderately Satisfied" and "Satisfied." The research concludes that prioritizing Lead Time is important to meet the company’s strategic objectives and that the AHP tool is effective in the multicriteria evaluation of suppliers.